A continuous spectrum for nonhomogeneous differential operators in Orlicz-Sobolev spaces - Mihailescu, Mihai; Radulescu, Vicentiu (MATHEMATICA SCANDINAVICA, 2009)
We study the nonlinear eigenvalue problem $-(\mathrm{div} (a(| abla u|) abla u)=\lambda|u|^{q(x)-2}u$ in $\Omega$, $u=0$ on $\partial\Omega$, where $\Omega$ is a bounded open set in ${\mathsf R}^N$ with smooth boundary, $q$ is a continuous function, and $a$ is a nonhomogeneous potential. We establish sufficient conditions on $a$ and $q$ such that the above nonhomogeneous quasilinear problem has continuous families of eigenvalues. The proofs rely on elementary variational arguments. The abstract results of this paper are illustrated by the cases $a(t)=t^{p-2}\log (1+t^r)$ and $a(t)= t^{p-2} [\log (1+t)]^{-1}$.